Comparative Evaluation of Membrane Filtration on the Tertiary Treatment of Synthetic Secondary Effluent - Mortula, Maruf (2022)
Wastewater reuse is essential for sustainable water management. However, it requires tertiary treatment within the plant to ensure suitable water quality. This project aims to investigate the comparative performance of conventional tertiary treatment (sand filtration) against membrane filtration technology to demonstrate the viability of membrane treatment for wastewater reuse. Sand filtration along with two membrane filtrations, Nano Filtration (NF) and Reverse Osmosis (RO), were tested for their efficiency in removing the target pollutants: chromium, phosphate, and UV-254 from secondary effluent. Standard medium-sized laboratory setups were used. Synthetic secondary effluent was used for comparison among the different treatment processes. The synthetic effluent was compared to the real wastewater to demonstrate the reliability of using synthetic effluent. Evaluation of the role of time and pressure on the treatment efficiency was also examined. Based on the experimental results, RO had the highest removal efficiency for all pollutants with more than 90% removal. The experimental results also showed that synthetic wastewater was reliable in representing the treatability of real wastewater. Time did not seem to have an impact on the quality of filtration. Moreover, as pressure increased there was a slight increase in the efficiency. This trend was observed in all pollutants except UV-254. ANOVA showed different results of the effect of pressure on the removal efficiency in both RO and NF as well as time in NF.